Exploring Learning Physics Concepts Through the Local Wisdom of East Kalimantan Culture: Traditional Weapons, Sumpit - Putri, Rahmah Trinita; Safitri, Afaurina Indriana; A'yun, Septy Kurrota; Suprapto, Nadi; Admoko, Setyo (FKIP Universitas Lampung, 2024)
Cultural diversity in Indonesia is due to the many islands that consist of various ethnicities, religions, and backgrounds. This cultural diversity can be a source of learning that can increase students' understanding and motivation to learn. One of the sciences that can be used to integrate with cultural diversity or local wisdom is physics. Physics is able to explain scientifically how a phenomenon in local culture occurs. Unfortunately, the integration of physics in local culture is still rare. Through this research, it is expected that there will be more references that discuss the integration of physics concepts in various types of local cultures. The purpose of this research is to identify and analyse physics concepts in the local culture of East Kalimantan people, especially the traditional weapon of sumpit. This research uses a qualitative descriptive research method oriented towards the exploration of physics concepts. Primary data in this study was obtained through interviews to find out how to use sumpit properly and correctly. The interviewees were selected using purposive sampling technique. Data was also collected through experiments to prove the concepts of physics contained in the traditional weapon of sumpit. Based on the results of the interview, it was found that sumpit are currently not used as weapons, but have developed into traditional games by the local community. In the traditional game of sumpit from East Kalimantan, physics concepts were analysed in the stages of using sumpit. Starting from the start of lifting the sumpit, blowing the sumpit, the movement of the damak inside the sumpit, the process of the damak coming out of the sumpit, to when the damak hits the target. From the results of the analysis, several physics concepts are obtained that occur during the process of using chopsticks, namely in the physics of mechanics, the concepts of parabolic motion, force, effort, momentum and collision, simple aircraft, and kinetic energy are used. In fluid physics, the concepts of aerodynamics and gas pressure are used. In wave physics, the concept of sound waves is used. Based on the results and discussion, it can be concluded that every movement and condition that occurs when sumpit can be studied physically. Therefore, the exploration of physics concepts in local wisdom needs to be improved to increase the reference of teaching materials on physics material. Keywords: sumpit, local wisdom, physics concept.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp264-284